Evaluation of whole body vibration and back pain problem among Light Rapid Transit (LRT) drivers - Jalil, Azlis-Sani; Zaid, Muhammad Firdaus; Yahya, Musli Nizam; S. M. Ismail, S. M. Sabri; Ahmad Tajedi, Noor Aqilah; Abdul Aziz, Roseni; Md Zein, Raemy (Trans Tech Publications, 2015)
A cross sectional study was conducted to evaluate whole body vibration (WBV) and back pain problem among light rail transit (LRT) driver. This study was carried out to determine exposure level of whole body vibration and identify back pain problem due to whole body vibration exposure among LRT driver. Standardized Nordic questionnaire was used for the analysis of musculoskeletal symptoms, to identify the prevalence of back pain, information about health history, working time duration, and working experiences was obtained from 52 drivers of light rail transit (LRT) train. HVM 100 Larson Davis was used to measure whole body vibration measurement of eight LRTs with different vehicle number. The measurement of whole body vibration was done during operation working time. The data collected from HVM 100 were transferred to the Blaze software for getting the vibration magnitude of the experiment while data collected from survey were analyzed by using Statistical Package for the Social Sciences (SPSS) for statistical analysis. The analysis of graph patterns and the differentiation of magnitude value from each LRT were studied to determine the exposure level of vibration. A high prevalence of back pain (82.7%) among LRT drivers was found and high daily exposure level was obtained. The finding showed that, there are relations between back pain and daily vibration exposure which resulted in a correlation coefficient of 0.709, with significant at α = 0.05. In conclusion, it was expected that the individuals subjected to the high vibration levels would tend to report back pain.